Low prevalence of rheumatoid arthritis in black-Caribbeans compared with whites in inner city Manchester. - MacGregor, A J (1994)
OBJECTIVE--To compare the prevalence of rheumatoid arthritis (RA) in Black-Caribbeans and Whites living in the same urban area. METHODS--Cases of inflammatory joint disease were ascertained initially from a postal screening survey of 1851 Black and 1829 age and sex-matched non-Blacks identified from general practice age-sex registers of seven general practices in the Moss Side and Hulme districts of Manchester. The ethnicity of respondents was confirmed using data from a postal screening questionnaire. Those reporting joint swelling or a history of arthritis were reviewed by a rheumatologist at surgeries held in each practice. The clinical records of the questionnaire non-responders and questionnaire-positive non-attenders at surgery were reviewed. RESULTS--In an adjusted denominator population of 1046 Black-Caribbeans and 997 Whites, the cumulative prevalence of RA was 2.9/1000 in Black-Caribbeans and 8/1000 in Whites, representing a prevalence in Black-Caribbeans of 0.36 times that found in Whites (95% confidence interval 0.1-1.3). CONCLUSIONS--Rheumatoid arthritis occurs less commonly in Black-Caribbeans than in Whites. The findings are consistent with published studies showing a low RA prevalence in rural African Black populations.